Modal Sosial dan Dinamika Usaha Mikro Kecil - Abidin, Djainal (Masyarakat: Jurnal Sosiologi, 2010)
The results of this research prove there is a statistically positive relationship between social capitals with increasing revenue. Social capital had a positive role for physical capital and education, as well as its contribution in creating greater business profits. The study also found the influence of social capital (23%), physical capital (11%) and capital or other variables (66%) for business profits. In conclusion, social capital as an asset has the potency to complement or replace the business assets, as we know it in today’s modern business world. In order to be an asset, it is necessary to establish a forum to provide certification of social capital on SME so it would work together with other economic assets in business activities.